Closed-loop recyclable full-bio-based glass high polymer material as well as preparation method, recycling method and application thereof

By constructing a hyperbranched network structure under catalyst-free conditions, epoxy resin-based glass polymer materials were prepared and recovered, which solved the problems of difficulty in material recycling and poor performance, and achieved closed-loop recycling, shape memory and self-healing capabilities, which were in line with the concept of green and sustainable development.

CN119529238AActive Publication Date: 2025-02-28BEIJING FORESTRY UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411871182.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Existing epoxy resin-based glass polymer materials have difficulties in recycling and require catalysts to improve performance, but the catalysts will reduce the thermal stability and mechanical properties of the material and pose a potential threat to the environment and health.

Method used

By reacting with glycerol and dimeric acid in catalyst-free conditions, a hyperbranched network structure is constructed to realize the preparation and recovery of epoxy resin-based glass polymer materials.

Benefits of technology

The closed-loop recycling, shape memory and self-healing ability of epoxy resin glass polymer materials has been achieved, solving the problems of difficulty in recycling traditional materials and poor performance, while avoiding the use of catalysts, which is in line with the concept of green and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a full-bio-based glass-like high polymer material capable of being recycled in a closed-loop mode and a preparation method, a recycling method and application of the full-bio-based glass-like high polymer material. The method comprises the following steps that lignin micromolecule acid alcohol diglycidyl ether reacts with glycerol and dimer acid under the condition of no catalyst, the full-bio-based glass high polymer material capable of being recycled in a closed loop manner is obtained. According to the invention, the problems of catalyst toxicity and poor mechanical properties of epoxy resin glass polymer materials are effectively solved. The raw materials used in the invention are all derived from biomass, and waste and damaged materials can be recycled due to closed-loop recycling capacity, so that the green sustainability of the materials is greatly improved, and the method has wide application prospects in the field of replacing traditional epoxy resin materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a closed-loop recyclable all-biobased glass-like polymer material and a preparation method, a recycling method and application thereof, belonging to the technical field of biobased polymer materials. Background Art

[0002] Epoxy resin has excellent mechanical properties, solvent resistance, heat resistance, chemical stability and low curing shrinkage, and is widely used in coatings, adhesives, composite materials and other fields. Due to its permanent cross-linked network structure after curing, it is difficult to degrade and recycle. Most industries use landfill or incineration to dispose of waste epoxy resin, which not only wastes resources but also pollutes the environment. Therefore, the preparation of a polymer material that can be recycled green and has the performance of traditional epoxy resin has received extensive attention and research.

[0003] In 2011, Leibler's research team embedded reversibly cross-linked dynamic ester bonds in the cross-linked network of thermosetting polymer materials to prepare recyclable epoxy resins. It exhibits rheological behavior similar to glass at high temperatures, so it is named "glass-like polymer materials", also known as glass-like polymers. At present, researchers have constructed a variety of β-hydroxy ester bond epoxy resin glass-like polymer materials, realizing the self-repair and recycling of epoxy resins. However, due to the low bond energy of the β-hydroxy ester dynamic covalent bond, its mechanical strength, cross-linking density and modulus are reduced after it is introduced into the epoxy resin. In addition, the current reports of epoxy resins based on β-hydroxy ester bonds usually require catalysts such as tin salts, zinc salts, tertiary amines, organic proton acids and triphenylphosphine to accelerate the rate of ester exchange reactions. These catalysts not only reduce the thermal stability and mechanical properties of the materials, but also bring safety hazards to human health and environmental pollution. Therefore, it is urgent to find a method for preparing high-strength epoxy resin glass-like polymer materials based on β-hydroxy ester bonds without the need for external catalysts.

[0004] Hyperbranched polymers have highly branched network structures, a large number of active end groups in the branches that can be modified, and unique microporous structures inside. They have the characteristics of less molecular chain entanglement, good solubility, low viscosity, and high chemical reactivity. In addition, the use of hyperbranched polymers to toughen and strengthen epoxy resins has been a research hotspot in recent years. Therefore, the use of hyperbranched epoxy resin-like glass polymer materials is expected to solve the problem of difficult recycling of high-performance epoxy resins. Summary of the invention

[0005] In view of this, the main purpose of the present invention is to provide a closed-loop recyclable all-bio-based glass polymer material and its preparation method, recycling method and application. The technical problem to be solved is to use renewable biomass resources as raw materials and to prepare an all-bio-based epoxy resin glass polymer material without a catalyst. By constructing a hyperbranched network structure, the numerous side chains contain abundant terminal hydroxyl groups, which catalyze the transesterification reaction without a catalyst, thereby giving the material excellent mechanical properties, shape memory, closed-loop recyclability and other properties.

[0006] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing a closed-loop recyclable all-biobased glass polymer material, comprising the following steps:

[0007] Lignin small molecule acid alcohol diglycidyl ether reacts with glycerol and dimer acid in the absence of a catalyst to obtain the closed-loop recyclable all-biobased glass-like polymer material.

[0008] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.

[0009] Preferably, the aforementioned method for preparing the closed-loop recyclable all-biobased glass polymer material comprises the following steps:

[0010] Step 1: Evenly mix lignin small molecule acid alcohol, epichlorohydrin and a catalyst, control the reaction temperature at 90-120°C, stir and react for 1-3h, cool to 0-20°C in an ice bath, add sodium hydroxide aqueous solution, and continue to react at 0-20°C for 3h; after the reaction, extract, wash, separate, dry, vacuum distill and recrystallize to obtain lignin small molecule acid alcohol diglycidyl ether;

[0011] Step 2, dissolving the lignin small molecule acid alcohol diglycidyl ether obtained in step 1 in a solvent, stirring evenly with glycerol at room temperature, and then reacting at 70-120°C for 1-2h, then adding dimer acid, continuing the reaction for 1-2h, and curing at 60-160°C for 3-48h to obtain a fully bio-based glass polymer material that can be closed-loop recycled.

[0012] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.

[0013] Preferably, in the aforementioned method for preparing a closed-loop recyclable all-biobased glass polymer material, in step 1, the concentration of the sodium hydroxide aqueous solution is 20wt%-50wt%.

[0014] Preferably, in the aforementioned method for preparing a fully bio-based glass-like polymer material that can be recycled in a closed loop, in step one, the catalyst is selected from one of tetrabutylammonium bromide, tetrabutylammonium iodide, benzyltrimethylammonium chloride and benzyltriethylammonium chloride, and the molar amount of the catalyst is 1-5% of the total molar amount of hydroxyl and carboxyl groups in the lignin small molecule acid alcohol.

[0015] Preferably, in the aforementioned method for preparing a fully bio-based glass-like polymer material that can be recycled in a closed loop, the lignin small molecule acid alcohol is selected from at least one of coumaric acid, ferulic acid, sinapinic acid, tetrahydrocurcumin, p-coumaryl alcohol, coniferyl alcohol and sinapinic alcohol.

[0016] Preferably, in the aforementioned method for preparing a closed-loop recyclable all-biobased glass polymer material, in step 1, the reaction temperature before ice bath cooling is 90-110° C., and the reaction time is 1-2 h.

[0017] Preferably, in the aforementioned method for preparing a fully bio-based glass polymer material that can be recycled in a closed loop, in step 2, the solvent is selected from one of ethyl acetate, anhydrous ethanol and N,N-dimethylformamide.

[0018] Preferably, in the aforementioned method for preparing a closed-loop recyclable all-biobased glass-like polymer material, in step 2, the lignin small molecule acid alcohol diglycidyl ether is evenly mixed with glycerol and dimer acid in a molar ratio of epoxy group / hydroxyl group / carboxyl group of (0.6-1):0.5:0.5.

[0019] Preferably, in the aforementioned method for preparing a closed-loop recyclable all-biobased glass-like polymer material, in step 2, the dimer acid is selected from one of Pripol 1004, Pripol 1006, Pripol 1025 and Pripol 1022VEG.

[0020] Preferably, in the aforementioned method for preparing a closed-loop recyclable all-biobased glass polymer material, in step 2, the curing temperature is 120-160° C., and the curing time is 8-12 hours.

[0021] Preferably, the aforementioned method for preparing a fully bio-based glass polymer material that can be recycled in a closed loop, wherein.

[0022] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a closed-loop recyclable all-bio-based glass polymer material, which has a hyperbranched network structure, a tensile strength of 34.8 to 72.5 MPa, and an elongation at break of 51.6% to 108%; the closed-loop recyclable all-bio-based glass polymer material is prepared by the above method.

[0023] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a friction nanogenerator, the friction nanogenerator includes a positive electrode, the positive electrode is composed of a closed-loop recyclable all-bio-based glass polymer material; the closed-loop recyclable all-bio-based glass polymer material has a hyperbranched network structure, a tensile strength of 34.8 to 72.5 MPa, and an elongation at break of 51.6% to 108%.

[0024] The purpose of the present invention and the technical problems solved are achieved by adopting the following technical solutions. The present invention proposes a method for recycling a fully bio-based glass polymer material that can be recycled in a closed loop, comprising the following steps: adding the above fully bio-based glass polymer material that can be recycled in a closed loop and a solvent together into a high-pressure reactor, wherein the alcohol hydroxyl group in the solvent undergoes a bond exchange reaction with the ester group in the β-hydroxy ester bond to degrade the cross-linked network structure into small molecules, and after removing the solvent, solidifying again to obtain a recyclable fully bio-based glass polymer material.

[0025] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.

[0026] Preferably, in the aforementioned closed-loop recyclable all-biobased glass polymer material recycling method, the solvent is selected from one of ethanol and methanol, the reaction temperature is 140-180° C., and the degradation reaction time is 6-10 h.

[0027] Compared with the prior art, the closed-loop recyclable all-biobased glass polymer material and its preparation method, recycling method and application described in the present invention have the following beneficial effects:

[0028] The fully bio-based glass polymer material that can be closed-loop recycled and obtained by the above method has a hyperbranched network structure rich in hydroxyl groups, which gives the material the ability of ester exchange, so that the epoxy resin glass polymer material can be closed-loop recycled, has shape memory and self-healing ability. It effectively solves the problems of the recycling difficulties of traditional epoxy resin materials and the poor mechanical properties and catalyst toxicity of epoxy resin glass polymer materials. The fully bio-based glass polymer material obtained by this method is completely derived from non-toxic and biocompatible biomass raw materials, which conforms to the concept of green and sustainable development.

[0029] The fully bio-based glass polymer material which can be recycled in a closed loop and is prepared by the present invention has a hyperbranched network structure, a tensile strength of 34.8 to 72.5 MPa, and an elongation at break of 51.6% to 108%.

[0030] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The preparation route of ferulic acid diglycidyl ether and epoxy resin in Example 1 of the present invention;

[0032] Figure 2 is the infrared spectrum of ferulic acid and ferulic acid diglycidyl ether in Example 1 of the present invention;

[0033] Figure 3 This is a stress-strain curve diagram of the all-biobased glass-like polymer material in Example 1 of the present invention;

[0034] Figure 4 This is a diagram of lifting a 10kg weight of the all-biobased glass polymer material in Example 1 of the present invention;

[0035] Figure 5 This is a self-healing diagram of the all-biobased glass-like polymer material in Example 1 of the present invention;

[0036] Figure 6 This is a diagram of the shape memory process of the all-biobased glass-like polymer material in Example 1 of the present invention;

[0037] Figure 7 Schematic diagram of chemical degradation and reprocessing of all-biobased glass-like polymer materials in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a closed-loop recyclable all-bio-based glass polymer material and its preparation method, recycling method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0039] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.

[0040] Some embodiments of the present invention provide a method for preparing a closed-loop recyclable all-biobased glass-like polymer material (Vitrimer), comprising the following steps:

[0041] (1) Add lignin small molecule acid alcohol, epichlorohydrin and catalyst in a molar ratio of 1:10:0.02 to 1:14:0.05 into a flask and mix them evenly. If the molar ratio of lignin small molecule acid alcohol, epichlorohydrin and catalyst is lower than 1:14:0.05, the reaction of lignin small molecule acid alcohol will be incomplete; if the molar ratio of lignin small molecule acid alcohol, epichlorohydrin and catalyst is higher than 1:10:0.02, the concentration of lignin small molecule acid alcohol and catalyst in the reaction system will be lowered, resulting in a decrease in reaction rate; the reaction temperature is controlled at 90-120°C. If it is lower than 90°C, the reaction of lignin acid alcohol compound will be incomplete, and if it is higher than 120°C, part of ferulic acid raw material will be decarboxylated; after stirring the reaction for 1-3h, if it is lower than 1h, the reaction of ferulic acid will be incomplete, and if it is higher than 3h, more by-products will be produced due to decarboxylation; ice bath cooling The temperature is cooled to 0-20°C. If the temperature is lower than 0°C, the hydroxide aqueous solution added subsequently will agglomerate, resulting in an incomplete ring-closing reaction. Adding an alkali metal hydroxide reaction system will release heat, resulting in an increase in the solution temperature. Under high temperature alkaline conditions, the ester bond in the intermediate product of ferulic acid diglycidyl ether is easily hydrolyzed and broken. If the temperature is higher than 20°C, the reaction will be more violent, generating a large amount of heat, causing the solution temperature to rise, resulting in the production of by-products. Add 20wt%-50wt% sodium hydroxide aqueous solution and continue to react at 0-20°C for 1-3h. If the temperature is lower than 0°C, the hydroxide aqueous solution will agglomerate, resulting in an incomplete ring-closing reaction. The reaction is an exothermic reaction. If the temperature is higher than 20°C, the temperature is too high, resulting in the production of by-products. If the temperature is lower than 1h, the intermediate product will not be completely closed, and the yield of the target product will be low. Within 3h, the intermediate product is basically completely closed, and the reaction is completed. If the temperature is higher than 3h, it will lead to a waste of resources. After the reaction, extraction, water washing, liquid separation, drying, reduced pressure distillation and recrystallization are performed to obtain lignin small molecule acid alcohol diglycidyl ether, which is a white solid; the above-mentioned reaction temperature is preferably 90-110°C. Within this reaction temperature range, the raw material conversion rate is high and the product yield is high; the reaction time is 1-2h. Within this reaction time range, the raw material can be completely converted into the target product with less by-products.

[0042] (2) dissolving the lignin small molecule acid alcohol diglycidyl ether obtained in step (1) in a solvent, stirring evenly with glycerol at room temperature, and then reacting at 70-120° C. for 1-2 h. If the temperature is lower than 70° C., the glycerol cannot be completely consumed. If the temperature is 70-120° C., the glycerol can react completely. If the temperature is higher than 120° C., it will lead to waste of resources. If the temperature is lower than 1 h, the glycerol cannot be completely consumed. If the temperature is 1-2 h, the glycerol can react completely. If the temperature is higher than 2 h, it will lead to waste of resources. Then, add dimer acid, continue to react for 1-2 h, pour into a mold, and if the temperature is lower than 1 h will make the dimer acid and prepolymer mix unevenly, 1-2h can make the dimer acid and prepolymer mix evenly, and more than 2h will lead to waste of resources; curing in a 60-160℃ oven for 3-48h, below 60℃ will make the material incompletely cured, 60-160℃ can make the material completely cured, and above 160℃ will lead to waste of resources; below 3h will lead to incomplete curing, 3-48h can achieve complete curing and obtain the best performance, and more than 48h will lead to waste of resources; a fully bio-based glass polymer material that can be recycled in a closed loop is obtained. Preferably, the aforementioned curing reaction temperature is 120-160℃, and preferably this temperature range allows the material to be completely cured and obtain the best performance. The reaction time is 8-12h, and preferably this time range allows the material to be completely cured and obtain the best performance.

[0043] In some embodiments, in order to ensure the reaction efficiency, the catalyst in the above step (1) can be selected from one of tetrabutylammonium bromide, tetrabutylammonium iodide, benzyltrimethylammonium chloride and benzyltriethylammonium chloride, and the molar amount of the catalyst is 1-5% of the total molar amount of hydroxyl and carboxyl groups in the lignin small molecule acid alcohol; less than 1% will cause incomplete reaction of ferulic acid, 1-5% can make all ferulic acid and epichlorohydrin react completely, and more than 5% will lead to waste of resources.

[0044] In some embodiments, the lignin small molecule acid alcohol in the above step (1) can be selected from at least one of coumaric acid, ferulic acid, sinapinic acid, tetrahydrocurcumin, p-coumarol, coniferyl alcohol and sinapinic alcohol. These monomers are biomass raw materials, which can react with epichlorohydrin to obtain epoxy group-terminated lignin small molecule acid alcohol diglycidyl ether raw materials. Factors to be considered: source lignin biomass, two functionalities, benzene rings, high reactivity, and can react with epichlorohydrin.

[0045] In some embodiments, in order to ensure the uniformity of the product, the solvent in the above step (2) can be selected from one of ethyl acetate, anhydrous ethanol and N,N-dimethylformamide.

[0046] In some embodiments, in order to improve product performance, the lignin small molecule acid alcohol diglycidyl ether in the above step (2) is mixed evenly with glycerol and dimer acid according to the molar ratio of epoxy group / hydroxyl group / carboxyl group (0.6-1):0.5:0.5. If the proportion of epoxy group is lower than 0.6, the tensile strength of the material will be reduced; if the proportion of epoxy group is higher than 1, the material will become brittle; the lignin small molecule acid alcohol diglycidyl ether is derived from lignin biomass, has two functionalities, has a benzene ring, and can react with epoxy groups.

[0047] In some embodiments, the dimer acid in the above step (2) can be selected from one of Pripol 1004, Pripol 1006, Pripol 1025 and Pripol 1022VEG; all of which are dimer acids and can increase flexibility for the target polymer.

[0048] In some embodiments, in the above step (2), the material used for the mold can be stainless steel or polytetrafluoroethylene, which is resistant to high temperatures and can shape the polymer material at high temperatures.

[0049] In the above technical scheme, the present invention prepares a fully bio-based glass-like polymer material that can be closed-loop recycled by reacting lignin small molecule acid alcohol diglycidyl ether with glycerol and dimer acid in the absence of a catalyst.

[0050] The closed-loop recyclable bio-based glass polymer material prepared by the present invention is added to a high-pressure reactor, and the alcoholic hydroxyl groups in the solvent undergo a bond exchange reaction with the ester groups in the β-hydroxy ester bond, thereby degrading the cross-linked network structure into small molecules. After the solvent is removed, the material is solidified again and can be recycled to obtain a regenerated fully bio-based glass polymer material. The closed-loop recyclable fully bio-based glass polymer material prepared by the present invention has a hyperbranched network structure containing abundant hydroxyl groups, which gives the material the ability of ester exchange, so that the epoxy resin glass polymer material exhibits closed-loop recycling, shape memory and self-healing capabilities. It effectively solves the problems of the difficulty in recycling traditional epoxy resin materials, the poor mechanical properties of epoxy resin glass polymer materials, and the toxicity of catalysts. Moreover, the material obtained by this method is completely derived from non-toxic and biocompatible biomass raw materials, which conforms to the concept of green and sustainable development.

[0051] Some embodiments of the present invention also provide a closed-loop recyclable all-biobased glass polymer material, wherein the closed-loop recyclable all-biobased glass polymer material is prepared by the above method, and the preparation process and structure are as follows: Figure 1As shown. The materials in Examples 1-3 all have a hyperbranched network structure, good mechanical properties (tensile strength can reach 34.8-72.5MPa, elongation at break is 51.6%-108%), and self-healing function. On the contrary, the material in Comparative Example 1 does not have a hyperbranched network structure, the tensile stress is only 0.8MPa, and it does not have a self-healing function. In addition, the material recovery efficiency obtained in Example 3 and Comparative Example 1 can reach more than 90%.

[0052] Some embodiments of the present invention also provide a friction nanogenerator, which includes a positive electrode, and the positive electrode is composed of a fully bio-based glass polymer material that can be recycled in a closed loop; the fully bio-based glass polymer material that can be recycled in a closed loop has a hyperbranched network structure, a tensile strength of 34.8 to 72.5 MPa, and an elongation at break of 51.6% to 108%.

[0053] Some embodiments of the present invention also provide a method for recycling a fully bio-based glass polymer material that can be recycled in a closed loop, comprising the following steps: adding the above fully bio-based glass polymer material that can be recycled in a closed loop and a solvent together into a high-pressure reactor, wherein the alcohol hydroxyl group in the solvent undergoes a bond exchange reaction with the ester group in the β-hydroxy ester bond, degrading the cross-linked network structure into small molecules, and after removing the solvent, re-solidifying and recycling to obtain a regenerated fully bio-based glass polymer material. In this way, the discarded or broken materials can be degraded by the solvent, re-solidified and reused, avoiding waste of resources.

[0054] In some embodiments, to ensure degradation efficiency, the solvent in the above steps can be selected from one of ethanol and methanol, the reaction temperature is 140-180°C, and the degradation reaction time is 6-10h; below 140°C, the material cannot be completely degraded; above 180°C, it will lead to waste of resources; below 6h, the material degradation is incomplete, and above 10h, the material can be completely degraded into small molecules. The preferred temperature is 160-180°C. In this temperature range, the polymer material is degraded more thoroughly and completely. The reaction time is 8-10h. During this period of time, the polymer material is completely depolymerized.

[0055] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0056] Example 1

[0057] This embodiment provides a method for preparing a closed-loop recyclable all-biobased glass polymer material, comprising the following steps:

[0058] Ferulic acid (50g, Shanghai Aladdin Reagent Co., Ltd.), epichlorohydrin (330g) and tetrabutylammonium iodide (1.7g) were added to a flask and mixed evenly. The reaction temperature was controlled at 110°C. After stirring for 3h, the mixture was cooled to 20°C in an ice bath, and a 40wt% aqueous sodium hydroxide solution (152g) was added. The mixture was continued to react at 20°C for 3h. After the reaction was completed, 500ml of ethyl acetate was added for extraction, and then the mixture was washed three times with 100ml of deionized water. The organic phase was transferred to a beaker, 10g of anhydrous magnesium sulfate was added for drying, and then ethyl acetate and epichlorohydrin were removed by a rotary evaporator (80°C, -0.1MPa) to obtain a crude product, ferulic acid diglycidyl ether. Subsequently, 100ml of ethyl acetate was used to dissolve the crude product obtained in the above steps at 80°C, and a white solid was precipitated out after cooling to room temperature. The solution was removed by filtration, and the purified product, ferulic acid diglycidyl ether, was obtained after drying. After dissolving 1g of the obtained ferulic acid diglycidyl ether in ethyl acetate (1g), stirring evenly with 0.216g of glycerol at room temperature, then reacting at 70°C for 1h, then adding 2g of Pripol 1006, continuing to react for 1h, pouring into a polytetrafluoroethylene mold, placing in a vacuum drying oven, vacuuming at 60°C to remove bubbles, heating to 160°C at a rate of 10°C / min, and then curing at 160°C for 12h to obtain a yellow transparent film material, that is, the closed-loop recyclable all-biobased glass polymer material. The all-biobased glass polymer material can be used in the preparation of positive electrode materials for friction nanogenerators.

[0059] like Figure 2 As shown in the infrared spectrum of ferulic acid, the hydroxyl group in ferulic acid is at 3432 cm -1 The characteristic absorption peak at 910 cm -1 A new characteristic absorption peak appeared at , proving that ferulic acid diglycidyl ether was successfully synthesized. The mechanical properties were tested at an experimental speed of 10 mm / min according to GB / T1040.3-2006. The obtained closed-loop recyclable all-biobased glass-like polymer material was subjected to a tensile test, and its tensile strength was 69.8 MPa ( Figure 3 ), and the elongation at break was 57.2%. The rectangular spline (5cm (length) × 1cm (width) × 0.1cm (thickness)) easily lifted a 10kg weight without breaking, proving its excellent mechanical strength ( Figure 4 ). After the closed-loop recyclable all-biobased glass polymer material was scratched (the scratch width was about 150 μm), it was placed in a 160°C oven and heated for 180 minutes, and the scratch was almost completely healed ( Figure 5 ).like Figure 6As shown, the closed-loop recyclable all-biobased glass-like polymer material achieves conversion between permanent deformation and temporary deformation at two temperatures of 95°C and 160°C.

[0060] Example 2

[0061] This embodiment provides a method for preparing a closed-loop recyclable all-biobased glass polymer material, comprising the following steps:

[0062] Ferulic acid (30g, Shanghai Aladdin Reagent Co., Ltd.), epichlorohydrin (198g) and tetrabutylammonium iodide (1.02g) were added to a flask and mixed evenly. The reaction temperature was controlled at 110°C. After stirring for 3h, the mixture was cooled to 20°C in an ice bath, and a 40wt% aqueous sodium hydroxide solution (91.2g) was added. The mixture was continued to react at 20°C for 3h. After the reaction was completed, 300ml of ethyl acetate was added for extraction, and then washed three times with 60ml of deionized water. The organic phase was transferred to a beaker, 6g of anhydrous magnesium sulfate was added for drying, and then ethyl acetate and epichlorohydrin were removed by a rotary evaporator (80°C, -0.1MPa) to obtain a crude product, ferulic acid diglycidyl ether. Subsequently, 60ml of ethyl acetate was used to dissolve the crude product obtained in the above steps at 80°C, cooled to room temperature to precipitate a white solid, filtered to remove the solution, and dried to obtain a pure product, ferulic acid diglycidyl ether. 1.6g of the obtained ferulic acid diglycidyl ether was dissolved in ethyl acetate (1g), and then stirred evenly with 0.432g of glycerol at room temperature, and then reacted at 70°C for 1h, and then 4g of Pripol 1006 was added, and after continuing to react for 1h, it was poured into a polytetrafluoroethylene mold, placed in a vacuum drying oven, and vacuumed to remove bubbles at 60°C under reduced pressure (-0.1MPa), and then heated to 150°C at a rate of 5°C / min, and then cured at 150°C for 12h to obtain a yellow transparent film material, that is, the closed-loop recyclable all-biobased glass polymer material. The all-biobased glass polymer material can be used in the preparation of positive electrode materials for friction nanogenerators.

[0063] The mechanical properties test was carried out at an experimental speed of 10 mm / min according to GB / T1040.3-2006. The obtained closed-loop recyclable all-bio-based glass polymer material was subjected to a tensile test, and its tensile strength was 34.8 MPa and its elongation at break was 108%. At the same time, after the closed-loop recyclable all-bio-based glass polymer material was scratched with a blade (the scratch width was about 100 μm), it was placed in an oven at 160°C and heated for 180 minutes, and the scratch was almost completely healed. The closed-loop recyclable all-bio-based glass polymer material achieves the conversion between permanent deformation and temporary deformation at two temperatures of 85°C and 150°C.

[0064] Example 3

[0065] This embodiment provides a method for preparing a closed-loop recyclable all-biobased glass polymer material, comprising the following steps:

[0066] Sinapic acid (10g, Shanghai Aladdin Reagent Co., Ltd.), epichlorohydrin (58g) and tetrabutylammonium iodide (0.3g) were added to a flask and mixed evenly. The reaction temperature was controlled at 110°C. After stirring for 3h, the mixture was cooled to 20°C in an ice bath, and a 40wt% aqueous sodium hydroxide solution (30g) was added. The mixture was continued to react at 20°C for 3h. After the reaction was completed, 100ml of ethyl acetate was added for extraction, and then the mixture was washed three times with 20ml of deionized water. The organic phase was transferred to a beaker, 2g of anhydrous magnesium sulfate was added for drying, and then ethyl acetate and epichlorohydrin were removed by a rotary evaporator (80°C, -0.1MPa) to obtain a crude product of sinapic acid diglycidyl ether. Subsequently, 20ml of ethyl acetate was used to dissolve the crude product obtained in the above steps at 80°C, and a white solid was precipitated out after cooling to room temperature. The solution was filtered to remove the solution, and the pure product sinapic acid diglycidyl ether was obtained after drying. After dissolving 1g of the obtained mustard acid diglycidyl ether in ethyl acetate (1g), stirring evenly with 0.09g of glycerol at room temperature, then reacting at 70°C for 1h, then adding 0.84g of Pripol1006, continuing to react for 1h, pouring into a polytetrafluoroethylene mold, placing in a vacuum drying oven, vacuuming at 60°C to remove bubbles, heating to 160°C at a rate of 10°C / min, and then curing at 160°C for 12h to obtain a yellow transparent film material, that is, the closed-loop recyclable all-biobased glass polymer material. The all-biobased glass polymer material can be used in the preparation of positive electrode materials for friction nanogenerators.

[0067] The mechanical properties test was carried out at an experimental speed of 10 mm / min according to GB / T1040.3-2006. The obtained fully bio-based glass polymer material that can be recycled in a closed loop was subjected to a tensile test, and its tensile strength was 72.5 MPa and its elongation at break was 51.6%. At the same time, the material was scratched with a blade (the scratch width was about 150 μm), and after being heated in an oven at 150°C for 180 minutes, the scratches on the surface of the material were basically completely healed. The fully bio-based glass polymer material that can be recycled in a closed loop realizes the conversion between permanent deformation and temporary deformation at two temperatures of 105°C and 170°C.

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a fully bio-based glass polymer material, comprising the following steps:

[0070] Ferulic acid (50g, Shanghai Aladdin Reagent Co., Ltd.), epichlorohydrin (330g) and tetrabutylammonium iodide (1.7g) were added to a flask and mixed evenly. The reaction temperature was controlled at 110°C. After stirring for 3h, the mixture was cooled to 20°C in an ice bath, and a 40wt% aqueous sodium hydroxide solution (152g) was added. The mixture was continued to react at 20°C for 3h. After the reaction was completed, 500ml of ethyl acetate was added for extraction, and then the mixture was washed three times with 100ml of deionized water. The organic phase was transferred to a beaker, 10g of anhydrous magnesium sulfate was added for drying, and then ethyl acetate and epichlorohydrin were removed by a rotary evaporator (80°C, -0.1MPa) to obtain a crude product, ferulic acid diglycidyl ether. Subsequently, 100ml of ethyl acetate was used to dissolve the crude product obtained in the above steps at 80°C, and a white solid was precipitated out after cooling to room temperature. The solution was filtered to remove the solution, and the purified product, ferulic acid diglycidyl ether, was obtained after drying. Take 1 g of the obtained ferulic acid diglycidyl ether and dissolve it in ethyl acetate (1 g), then stir it evenly with 2 g of Pripol 1006 at room temperature, then react at 70°C for 1 hour, pour it into a polytetrafluoroethylene mold, place it in a vacuum drying oven, reduce the pressure (-0.1 MPa) at 60°C to evacuate to remove bubbles, heat it to 160°C at a rate of 10°C / min, and then cure it at 160°C for 12 hours to obtain a yellow transparent film material.

[0071] According to GB / T1040.3-2006, the mechanical properties were tested at a test speed of 10 mm / min. The obtained material was subjected to a tensile test, and its tensile strength was only 0.8 MPa. At the same time, after the material was scratched with a blade (the scratch width was about 140 μm), it was difficult to heal after being placed in an oven at 160°C for 12 hours.

[0072] The closed-loop recyclable bio-based glass polymer materials prepared in Examples 1-3 and the material prepared in Comparative Example 1 were added to a high-pressure reactor respectively, and the temperature was raised to 180°C after ethanol was added. After reacting for 10 hours, the network structure of the material was depolymerized into small molecules. After removing the excess ethanol by rotary evaporation (60°C, -0.1MPa), the material was poured into a polytetrafluoroethylene mold, and placed in a 160°C oven and heated for 12 hours to solidify again to obtain a fully bio-based glass polymer material. The tensile strength of the closed-loop recyclable bio-based glass polymer material in Example 1 can be restored to 96% of the original strength, the tensile strength of the closed-loop recyclable bio-based glass polymer material in Example 2 can be restored to 97% of the original strength, the tensile strength of the closed-loop recyclable bio-based glass polymer material in Example 3 can be restored to 93% of the original strength, and the tensile strength of the material in Comparative Example 1 can be restored to 90% of the original strength. The process is as follows Figure 7 shown.

[0073] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.

[0074] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0075] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

[0076] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a closed-loop recyclable all-biobased glass polymer material, characterized in that: The following steps are involved: Lignin small molecule acid alcohol diglycidyl ether reacts with glycerol and dimer acid in the absence of a catalyst to obtain the closed-loop recyclable all-biobased glass-like polymer material.

2. The method for preparing a closed-loop recyclable all-biobased glass polymer material according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: Evenly mix lignin small molecule acid alcohol, epichlorohydrin and a catalyst, control the reaction temperature at 90-120°C, stir and react for 1-3h, cool to 0-20°C in an ice bath, add sodium hydroxide aqueous solution, and continue to react at 0-20°C for 3h; after the reaction, extract, wash, separate, dry, vacuum distill and recrystallize to obtain lignin small molecule acid alcohol diglycidyl ether; Step 2, dissolving the lignin small molecule acid alcohol diglycidyl ether obtained in step 1 in a solvent, stirring evenly with glycerol at room temperature, and then reacting at 70-120°C for 1-2h, then adding dimer acid, continuing the reaction for 1-2h, and curing at 60-160°C for 3-48h to obtain a fully bio-based glass polymer material that can be closed-loop recycled.

3. The method for preparing a closed-loop recyclable all-biobased glass polymer material according to claim 1, characterized in that: Step 1, the concentration of the sodium hydroxide aqueous solution is 20wt%-50wt%; the catalyst is selected from one of tetrabutylammonium bromide, tetrabutylammonium iodide, benzyltrimethylammonium chloride and benzyltriethylammonium chloride, and the molar amount of the catalyst is 1-5% of the total molar amount of hydroxyl and carboxyl groups in the lignin small molecule acid alcohol.

4. The method for preparing a closed-loop recyclable all-biobased glass polymer material according to claim 1, characterized in that: In step 1, the lignin small molecule acid alcohol is selected from at least one of coumaric acid, ferulic acid, sinapinic acid, tetrahydrocurcumin, p-coumaryl alcohol, coniferyl alcohol and sinapyl alcohol; the reaction temperature before ice bath cooling is 90-110° C., and the reaction time is 1-2 h.

5. The method for preparing a closed-loop recyclable all-biobased glass polymer material according to claim 1, characterized in that: In step 2, the solvent is selected from one of ethyl acetate, anhydrous ethanol and N,N-dimethylformamide; the lignin small molecule acid alcohol diglycidyl ether is evenly mixed with glycerol and dimer acid in a molar ratio of epoxy group / hydroxyl group / carboxyl group of (0.6-1):0.5:0.

5.

6. The method for preparing a closed-loop recyclable all-biobased glass polymer material according to claim 1, characterized in that: In step 2, the dimer acid is selected from one of Pripol 1004, Pripol 1006, Pripol 1025 and Pripol 1022VEG; the curing temperature is 120-160° C., and the curing time is 8-12 hours.

7. A closed-loop recyclable bio-based glass polymer material, characterized in that: The closed-loop recyclable all-biobased glass polymer material has a hyperbranched network structure, a tensile strength of 34.8 to 72.5 MPa, and an elongation at break of 51.6% to 108%. The closed-loop recyclable all-biobased glass polymer material is prepared by the method described in any one of claims 1 to 6.

8. A friction nanogenerator, characterized in that: The friction nanogenerator includes a positive electrode, which is composed of a fully bio-based glass polymer material that can be recycled in a closed loop; the fully bio-based glass polymer material that can be recycled in a closed loop has a hyperbranched network structure, a tensile strength of 34.8 to 72.5 MPa, and an elongation at break of 51.6% to 108%.

9. A closed-loop recycling method for all-biobased glass polymer materials, characterized in that: The method comprises the following steps: adding the closed-loop recyclable all-biobased glass polymer material as claimed in claim 7 and a solvent together into a high-pressure reactor, wherein the alcoholic hydroxyl groups in the solvent undergo a bond exchange reaction with the ester groups in the β-hydroxy ester bonds to degrade the cross-linked network structure into small molecules, and after removing the solvent, solidifying again to obtain a recyclable all-biobased glass polymer material.

10. The closed-loop recyclable all-biobased glass polymer material recycling method according to claim 9, characterized in that: The solvent is selected from one of ethanol and methanol, the reaction temperature is 140-180° C., and the degradation reaction time is 6-10 hours.

Citation Information

Patent Citations

  • Dimer acid modified epoxy resin and preparation method thereof

    CN106632154A

  • Intrinsic self-repairing hyperbranched epoxy resin as well as preparation method and application thereof

    CN107814911A

  • Bio-based hyperbranched polyester plasticizer prepared by adopting one-step method and application thereof in PVC cable material

    CN110922570A

  • Super-tough self-repairing epoxy resin glass polymer material and preparation method thereof

    CN112961463A

  • Bio-based hyperbranched polymer epoxy resin and preparation method thereof

    CN114395216A